Learning Nahwu Using The Book Of Murod Awamil ‎Mandaya Using The Sorogan Method At The Ardaniah Pusat Islamic Boarding School Serang-Banten, West Java - Purnomo, Jeri; Wasilah, Wasilah; Rohayati, Enok; Hidaya, Nur; Ramasepti, Winki (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
This research aims to describe the planning, process, and evaluation of nahwu learning using the Murod Awamil Mandaya book employing the Sorogan method at the Ardaniah Islamic Boarding School Center. This research uses qualitative research with a descriptive approach. Data was collected through observation, interviews, and documentation. Data analysis was conducted through three stages, namely data reduction, data presentation, and conclusion. The results of the research show that the planning of nahwu learning at the Ardaniah Islamic Boarding School Center has a structured plan, an intensive learning process, and a comprehensive evaluation. The learning planning already includes setting goals and selecting materials, methods, media, and assessments tailored to the needs of the students. The learning process utilizes the sorogan method, where learning is conducted directly and individually with intensive interaction between teachers and students. The learning evaluation is conducted through written, oral, and observation tests. Moreover, the evaluation is aligned with the cognitive, affective, and psychomotor domains of the students. Keywords: Nahwu learning, Murod Awamil Mandaya book, Sorogan method